Intersecção do sistema sociotécnico e inovação em práticas sociais no varejo de vestuário - Machado, Rafael Carvalho (2018)
The sustainability challenge is not just a technology issue. Technological solutions have proved to be insufficient to reduce the social and environmental impact of human activities, contributing to the consumption of natural and human resources above what the planet is capable of providing. In this sense, socio-eco-innovations – changes that improve the socio-environmental performance of activities – are developed beyond technology: in society's behavior. One of the sectors that has been widely questioned for its impact on both natural resources and the exploitation of human resources is the textile and clothing industry. In the case of Brazil, retailers assume this responsibility before society, on the one hand because it is closer to the final consumer that bears these questions and, on the other hand, because it is the strongest point in the production chain. In this way, the socio-eco-innovations in this industry was sought in retailing, through case study of a large national retailer. The study was developed based on the Sociotechnical Transition theory, using the multilevel perspective and on the Social Practice theories, seeking to understand the dynamics of the activities of production and diffusion of socio-ecoinovations. The qualitative perspective of the research used non-participant observations and interviews as methods of data collection and for the analysis were reconstructed practices identified and compared with the evolution of the process of transition to sustainability in the sector. With these analyzes, points of intersection between the sociotechnical system of clothing retail and the development of socio-eco-innovation practices were identified. The results were consistent with the theoretical approximations of the two theories, which identify the existence of points of intersection between sociotechnical regimes and landscape and the elements of social practices, creating a kind of lock-together that is capable of creating a kind of dependence of the trajectory in the emergence of socio-eco-innovations of niche. The study concluded that the two theoretical approaches, although not intended to be unified, allow a better understanding of a phenomenon and the translation of these points of intersection into understandings of social practice deserves attention from future studies.